Simplified drain current model for pinch‐off double gate junctionless transistor. Issue 2 (1st January 2014) - Sahu, C.; Swami, P.; Sharma, S.; Singh, J.
Abstract : A simplified analytical drain current model for the long‐channel pinch‐off junctionless (JL) double‐gate field effect transistor (DGFET) is proposed. The drain current is generally expressed in terms of the mobile charge density and it has been expressed in terms of the pinch‐off voltage and the gate capacitance. The proposed model is validated against TCAD simulation results, and is able to predict the behaviour of the JL DGFET for different bias conditions and device dimensions, accurately. The transconductance and the transconductance‐to‐drain‐current ratio are important parameters for analogue circuits, and have been calculated and exhibit good agreement with the TCAD results.